The Clinical Characteristics and Outcomes of Hemorrhagic Fever With Renal Syndrome in Pregnancy - Ren, Danfeng; Fu, Shan; Yan, Taotao; Ni, Tianzhi; Zhang, Ze; Zhang, Mengmeng; Zhou, Jingwen; Yang, Nan; Yang, Yuan; He, Yingli; Chen, Tianyan; Zhao, Yingren; et al. (Frontiers in Medicine, 2022)
Pregnant women with hemorrhagic fever with renal syndrome (HFRS) are a significant challenge for clinicians. The clinical characteristics of HFRS in pregnant women and its influence on both the pregnant women and fetus have yet to be clarified clearly. To highlight the specific clinical features of HFRS in pregnant women and the outcomes of pregnant women with HFRS and their fetuses, we screened pregnant women with HFRS from inception to May 1st 2021. We also conducted a comparison with non-pregnant women complicated with HFRS. Twenty-seven pregnant women and 87 non-pregnant women with complete electronic medical records were enrolled for final analyses; 55.6% (15/27) and 21.8% (19/87) were diagnosed as critical type in pregnant women and non-pregnant women, respectively. Compared with non-pregnant patients, there was a significantly higher likelihood of critical status in pregnant patients; the risk was significantly higher in late trimester (p < 0.001). In addition, hypoalbuminemia and anemia were also evident in pregnant patients (p = 0.04, p < 0.001, respectively). Leukocyte count, especially when higher than 15 × 109/L, was significantly correlated with disease severity (p = 0.009). After comprehensive therapy, 26 pregnant patients recovered without sequelae. Five fetal adverse events were reported during hospitalization. All adverse events were observed in mothers with critical types (p = 0.047, Χ2 =4.909) and occurred in the later trimester. Collectively, our data show that pregnant woman with HFRS during the third trimester presents a more severe condition, especially those with leukocytosis. However, the majority of those pregnant patients could recover with comprehensive treatment and undergo normal labor.